Consumer perception on Free Basic App: an empirical study on consumer perception on providing basic internet services to the non-internet users by Facebook - Ahmed, Alauddin (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.